Angloscene Compromised Personhood in Afro-Chinese Translations - Ke-Schutte, Jay (University of California Press, 2023)
Angloscene examines Afro-Chinese interactions within Beijing's aspirationally cosmopolitan student class. Jay Ke-Schutte explores the ways in which many contemporary interactions between Chinese and African university students are mediated through complex intersectional relationships with whiteness, the English language, and cosmopolitan aspiration. At the heart of these tensions, a question persistently emerges: How does English become more than a language-and whiteness more than a race? Engaging in this inquiry, Ke-Schutte explores twenty-first century Afro-Chinese encounters as translational events that diagram the discursive contours of a changing transnational political order-one that will certainly be shaped by African and Chinese relations. A tremendously nuanced book that moves beyond the verities of postcolonial theory as much as liberal illusions of postracialism in the academy. The ethnographic richness of Angloscene in its expositions of tropes and situated encounters is remarkable and pointed-even poignant." - DILIP M. MENON, editor of Changing Theory: Concepts from the Global South "Reflecting a critical sensibility from the Global South, Jay Ke-Schutte's book defies Euro-American-centric perspectives on language, race, and colonialism. The innovative concept of the Angloscene offers an imaginative way to unpack the transnational power matrix that conditions Afro-Chinese encounters." - FAN YANG, author of Faked in China: Nation Branding, Counterfeit Culture, and Globalization This book reveals the manner in which talk about signs of race and the racialization of those engaged in talk readily emerge hand in hand within social encounters, so that to isolate them from each other is to lose sight of the processes through which inequity persists in social life even when it is abjured." - ASIF AGHA, Francis E. Johnston Term Professor of Anthropology, University of Pennsylvania, and Editor-in-Chief, Signs and Society